m_Health Current and Future Applications - Andreoni, Giuseppe; Perego, Paolo; Frumento, Enrico (EAI/Springer Innovations in Communication and Computing, 2019)
This book describes current trends in m_Health technology, systems, and applications. The book proposes a multifaceted view on m-Health opportunities and requirements starting from four aspects: patient, technology, design and innovation. The analysis is completed by a market segmentation overview and by the most recent research experiences to offer a complete benchmark and vision of m_Health for today and tomorrow. The contributions are based on the outcomes of initiatives on the future of healthcare, funded by the EU in the frame of FP7 and Horizon 2020 and their deployment into real clinical practice. Throughout the book, clinicians, technicians, researchers, and end-users debate their experience, needs, risks, opportunities, and available solutions in this fast moving field. • Presents innovations, analysis, and applications using m_health solutions; • Provides a multidisciplinary approach by presenting technological aspects of m-health in adding to outcomes of clinical trials using m_health systems; • Discusses current innovation programs that supports citizens' empowerment through self-management of health and disease, health promotion, and disease prevention.